Strategic Implementation of NoSQL Technologies in Modern Enterprise Data Architectures (International Journal of Engineering & Extended Technologies Research (IJEETR), 2025)
Enterprise Data Management is undergoing a paradigm shift from relational database systems to NoSQL technologies. The present evaluation provides a systematic assessment of the NoSQL adoption journey undertaken by enterprises, with a specific focus on the architectural benefits of NoSQL, their performance characteristics, and their use cases in enterprise environments. This article confirms that performance enhancement is feasible with NoSQL systems based on the range of data models they implement, including key/value systems, document stores, column-family systems, and graph databases. Each data model addresses enterprise requirements while leveraging an architecture with horizontal scalability, flexible schema, and a data access pattern that is not efficient with relational systems. Each NoSQL database implementation contains architectural advantages that can provide enterprises with improved performance for targeted workloads, deploy microservices architecture in enterprise environments, and implement analytics with real-time capabilities. Although there are operational complexities involved with hybrid architectures as well as integration challenges associated with NoSQL technologies that enterprises must navigate when adopting NoSQL databases, the results show how the challenges associated with data consistency models, streaming architectures, and hybrid persistence strategies differ when utilizing both traditional and NoSQL systems with an operational downside.
Keywords: NoSQL Technologies; Enterprise Data Architecture; Database Performance; Distributed Systems; Hybrid Persistence